CONTENT ANALYSIS OF SHORT VIDEOS AS THE DOMINANT FORMAT FOR AUDIENCE ENGAGEMENT ON TIKTOK, IG REELS, AND YOUTUBE SHORTS: A LITERATURE REVIEW - Hadenan Towpek; Irda Suriani (Adisam Publisher, 2025)
This study examines short video content as the dominant format driving audience engagement on three major social media platforms: TikTok, Instagram Reels, and YouTube Shorts. Using a literature review method, this study analyses the technical characteristics and content formats of each platform, as well as the factors influencing user engagement levels. The findings reveal that while all three platforms share the core concept of vertical short videos, they each possess unique characteristics in terms of duration, editing features, distribution algorithms, and audience profiles that influence interaction patterns. TikTok is known for its high virality and strong content personalisation, Instagram Reels relies on visual aesthetics and social interaction, while YouTube Shorts combines short and long-form content to reach a broader audience. Factors such as visual quality, content relevance, popular music, and interactivity have proven significant in increasing audience engagement. This study provides a comprehensive understanding that is beneficial for content creators, digital marketers, and social media researchers in optimising digital communication strategies based on short videos.